The Impact of Wind Stress Feedback on the Stability of the Atlantic Meridional Overturning Circulation. - Arzel, Olivier; England, Matthew H.; Saenko, Oleg A. (Journal of Climate, 2011)
International audience Recent results based on models using prescribed surface wind stress forcing have suggested that the net freshwater transport Σ by the Atlantic meridional overturning circulation (MOC) into the Atlantic basin is a good indicator of the multiple-equilibria regime. By means of a coupled climate model of intermediate complexity, this study shows that this scalar Σ cannot capture the connection between the properties of the steady state and the impact of the wind stress feedback on the evolution of perturbations. This implies that, when interpreting the observed value of Σ, the position of the present-day climate is systematically biased toward the multiple-equilibria regime. The results show, however, that the stabilizing influence of the wind stress feedback on the MOC is restricted to a narrow window of freshwater fluxes, located in the vicinity of the state characterized by a zero freshwater flux divergence over the Atlantic basin. If the position of the present-day climate is farther away from this state, then wind stress feedbacks are unable to exert a persistent effect on the modern MOC. This is because the stabilizing influence of the shallow reverse cell situated south of the equator during the off state rapidly dominates over the destabilizing influence of the wind stress feedback when the freshwater forcing gets stronger. Under glacial climate conditions by contrast, a weaker sensitivity with an opposite effect is found. This is ultimately due to the relatively large sea ice extent of the glacial climate, which implies that, during the off state, the horizontal redistribution of fresh waters by the subpolar gyre does not favor the development of a thermally direct MOC as opposed to the modern case.